Optimizing students' mathematical critical and creative thinking skills through the flip-a-team model with e-learning - Arnellis, Arnellis; Syarifuddin, Hendra; Ismail, Rafki Nasuha (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
In the present digital age, the utilization of e-learning platforms in education is becoming increasingly significant. This is especially true in the field of Mathematics Education, where there exists a challenge to enhance students' critical and creative thinking abilities. This research aimed to investigate the improvement in students' critical and creative mathematical thinking abilities through the implementation of a team project-based model, Flip-a-Team, within UNP's e-learning platform. A quasi-experimental research design was used, applying a post-test control group approach. The sample involved 64 students from a mathematics study program who were enrolled in the July - December 2022 semester. These students were divided into two groups: 32 students in the experimental group (Class A) that was instructed through the Flip-a-team model, and 32 students in the control group (Class B) that experienced problem-based learning. Based on an independent t-test, the results demonstrated that the mathematical learning process incorporating the Flip-a-Team model had a positive and significant impact on the students' critical and creative mathematical thinking abilities. The Flip-a-Team model is recommended for implementation in mathematics instruction. The UNP e-learning platform could serve as a feasible solution for digitally based mathematics education, particularly in fostering students' critical and creative thinking abilities in mathematics.